Keterlibatan Hakim Perempuan Sebagai Pekerja Publik Sekaligus Istri Dalam Mencipatakan Keluarga Yang Harmonis Perspektif Hukum Islam - Gardeni, Alma Sari; Rofiah, Khusniati (Fakultas Syariah IAIN Ponorogo, 2024)
A female judge has a dual role when the judge is married. It's not just work that needs to be done. However, work as a wife and housewife must also be considered. A female judge certainly has high consequences for work. Not only is he responsible for his work, a judge must of course be ready to be transferred to various court areas throughout Indonesia. Moreover, a female judge, who is basically a woman, also plays an important role in the family, especially. For example, serving your husband and having to educate and give love to your children. The focus of the research is related to the role of female judges in earning a living and in creating family harmony when they have to be transferred to areas far from their families. This thesis is a qualitative research type of field research with a normative approach. Meanwhile, technical data collection involves conducting interviews and documentation. The analysis used in this research is descriptive analysis with an inductive method.